Casey Hocknell: capstone - Hocknell, Casey, artist (Colorado State University. Libraries, 2026)
The artist's statement: The human search for the divine, the nature of profound beauty, and organic processes have emerged as central themes of my paintings. Inspired by daily human ritualistic activities and processes of organic matter, my work draws attention to the divinity engulfed in otherwise mundane moments. The ambiguity within my work presents the viewer with a Rorschach-esque search for beauty and divine wonder. My purposeful lack of recognizable imagery leads the viewer to contemplate where beauty exists, and their own connection to ultimate reality. My body of work is exploration of the medium of paint and faces the question of what it means to make a painting. My investigation of oil paint primarily takes place through layering, additions of mediums, and my treatment of the surface I am working on. The material nature of oil paint creates a subtle thematic relationship to organic matter derived from the natural world uniting physical material and subject matter. Through these paintings I investigate interactions of shape and color reminiscent of the vegetal structures. My dynamic, fluid compositions echo the fleeting splendor of the natural world while the roughness of the canvas, and sporadic drips of layered paint starkly remind the viewer of the one dimensional nature of these objects. Referencing artists such as Helen Frankenthaler, and Georgia O'Keeffe I explore the power of paint and the range of possibilities within the medium.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting